Does Open Reduction and Internal Fixation versus Primary Arthrodesis Improve Patient Outcomes for Lisfranc Trauma? A Systematic Review and Meta‐analysis. Issue 6 (June 2016) - Smith, Nicholas; Stone, Craig; Furey, Andrew
Abstract: Background: Although Lisfranc injuries are uncommon, representing approximately 0.2% of all fractures, they are complex and can result in persistent pain, degenerative arthritis, and loss of function. Both open reduction and internal fixation (ORIF) and primary fusion have been proposed as treatment options for these injuries, but debate remains as to which approach is better. Questions/purposes: We asked whether ORIF or primary fusion led to (1) fewer reoperations for hardware removal; (2) less frequent revision surgery; (3) higher patient outcome scores; and (4) more frequent anatomic reduction. Methods: A systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. Three trials met the criteria for inclusion within the meta‐analysis. Qualifying articles for the meta‐analysis had data extracted independently by two authors (NS, AF). The quality of each study was assessed using the Center for Evidence Based Medicine's evaluation strategy; data were extracted from articles rated as good and fair: two and one article, respectively. Results: The risk ratio for hardware removal was 0.23 (95% confidence interval [CI], 0.11‐0.45; p < 0.001) indicating more hardware removal for ORIF than fusion. For other revision surgery, the risk ratio for ORIF was 0.36 (95% CI, 0.08‐1.59; p = 0.18) favoring neither. Similarly, neither was favored using patient‐reported outcomes; the standard mean difference was calculated to be 0.50 (95% CI, −2.13 to 3.12; p = 0.71). When considering the risk of nonanatomic alignment, neither was favored (risk ratio, 1.48; 95% CI, 0.34‐6.38; p = 0.60). Conclusions: The surgeon should consider the increased risk of hardware removal along with its associated morbidity and discuss this with the patient preoperatively when considering ORIF of Lisfranc injuries. Because no new trials have been performed since 2012, further randomized controlled trials will be needed improve our understanding of these interventions. Level of Evidence: Level I, therapeutic study.